Study of Watershed Characteristics Affecting the Hydrologic Performance - Tyagi, N.K; Raghunath, E; Lekhmanan, V. (Journal of Soil and Water Conservation, 2022)
The effect of watershed characteristics on the runoff yield has been reported by several research workers. Birford et al (1) studied the effect of shape, topography and drainage on runoff performance. Laurenson et al (2) took drainage area, length and slope of main stream, shape index, form factor and compactness coefficient as the significant factors that affect runoff. Synder (3) found that shape as it affects the runoff yield of watershed is related to distance along the main stream from outlet to the geographical centre of watershed. Horton (5) used the drainage pattern as the most siginificant single factor to describe the runoff performance. Some of these factors have been used here to make a comparative study of hydrologic performance of watershed in the Nilgiris.